A PIV investigation of the effect of disperse phase fraction on the turbulence characteristics of liquid–liquid mixing in a stirred tank. (2nd October 2016) - Liu, Nannan; Wang, Wei; Han, Jiacheng; Zhang, Meng; Angeli, Panagiota; Wu, Changchun; Gong, Jing
Abstract: In this paper, utilising 2D angle-resolved particle image velocimetry (PIV), the flow field of a dilute aqueous-in-oil dispersion is experimentally studied in a stirring tank. Opacity during liquid–liquid mixing is eliminated by matching the refractive indices of both phases. Anisotropy of the turbulence flow field is analysed via the turbulent kinetic energy (TKE) and energy dissipation rate (EDR) obtained at different measuring angles. The influence of spatial resolution is compared and discussed. TKE and EDR are observed to increase with increment of dispersed phase fraction while a small range of disorder and fluctuation is observed in the impeller region. The effect of dispersed droplets should be attributed to the strengthened fluctuation of velocities and spatial differences. Further work concerning higher resolution and the disperse fraction is necessary. Highlights: Flow field of dilute aqueous-in-oil dispersion is measured by PIV in stirred tank. Opacity during mixing is eliminated by matching refractive index of both phases. The influence of spatial resolution and angle-resolved plane are discussed. Disperse fraction enhanced turbulent kinetic energy and energy dissipation.